Analisis Penyusunan Rencana Strategis RSUD dr. M. Yunus Bengkulu Tahun 2021-2026 - Zahrotul Lina Andarwati; Dumilah Ayuningtyas (Universitas Pahlawan Tuanku Tambusai, 2023)
The focus of this manuscript is on developing a strategic plan for a hospital, with a case study of RSUD dr. M. Yunus Bengkulu, which is a government-owned Class B Education Hospital. This research is qualitative in nature with a descriptive design. The research findings indicate that both external and internal environmental factors position RSUD dr. M. Yunus Bengkulu in the